Italy - Winter, Jane Kohen, 1959-; Jermyn, Leslie; Spilling, Jo-Ann. (New York : Marshall Cavendish, 2014)
"Provides comprehensive information on the geography, history, wildlife, governmental structure, economy, cultural diversity, peoples, religion, and culture of Italy"--Provided by publisher.
Geography -- History -- Government -- Economy -- Environment -- Italians -- Lifestyle -- Religion -- Language -- Arts -- Leisure -- Festivals -- Food -- Map of Italy -- About the Economy -- About the Culture -- Time Line -- Glossary.
Includes bibliographical references and index.
Keywords: Italy -- Juvenile literature